2019
DOI: 10.1039/c9sm01210a
|View full text |Cite
|
Sign up to set email alerts
|

Active matter invasion

Abstract: Biological active materials such as bacterial biofilms and eukaryotic cells thrive in confined micro-spaces. Here, we show through numerical simulations that confinement can serve as a mechanical guidance to achieve distinct modes of collective invasion when combined with growth dynamics and the intrinsic activity of biological materials. We assess the dynamics of the growing interface and classify these collective modes of invasion based on the activity of the constituent particles of the growing matter. Whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 73 publications
(95 reference statements)
0
18
0
Order By: Relevance
“…The focus of our work lies on the internal structure and single-cell dynamics inside the sheet and how it is influenced by a bottleneck. Previous works, both experimental [9, 10, 11, 12, 17, 13, 14, 16] and numerical [25, 42], have concentrated on velocity and density fields or the shape of the invasion front in channels of constant [9, 10, 11, 12, 17, 13, 14, 16, 25, 42] or linearly changing [17, 25] diameter. In many of these studies strong density fluctuations in the channel are reported, a feature that our model did not reproduce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of our work lies on the internal structure and single-cell dynamics inside the sheet and how it is influenced by a bottleneck. Previous works, both experimental [9, 10, 11, 12, 17, 13, 14, 16] and numerical [25, 42], have concentrated on velocity and density fields or the shape of the invasion front in channels of constant [9, 10, 11, 12, 17, 13, 14, 16, 25, 42] or linearly changing [17, 25] diameter. In many of these studies strong density fluctuations in the channel are reported, a feature that our model did not reproduce.…”
Section: Discussionmentioning
confidence: 99%
“…These take into account fundamental symmetries and coarse-grained mesoscopic forces, which provide a larger-scale picture of the system, and they have already been shown to be applicable to cellular systems [36, 37, 38, 39, 18]. Continuum models have also been used to simulate the dynamics of active matter confined to elongated channels [40, 41] and to model invasion of active matter into a narrow straight capillary [42].…”
Section: Introductionmentioning
confidence: 99%
“…This free energy ensures that in the active nematic phase φ = 1, the orientational order is retained, while in the passive phase φ = 0, the magnitude of orientational order that minimizes the free energy -i.e. Q for which δF/δQ = 0 -diminishes to zero, resulting in an isotropic fluid [26,28]. In Figure 2b, we compare analytical results for the one-dimensional φ profile to the results from numerical integration of Eq.…”
Section: A Active Nematic Interfacesmentioning
confidence: 99%
“…The presence of an interface between two phases gives rise to additional stresses in the flow field. To capture these additional stresses, the back-coupling from the binary order parameter φ to the fluid flow equation is introduced through capillary stresses [25][26][27][28]:…”
Section: B Coupling To Hydrodynamicsmentioning
confidence: 99%
“…While previous analyses have focused on the experimentally tractable cases of unconfined and unsubmerged biofilms [1,2,10,11], they do not accurately reflect the conditions in which many biofilms grow; they thrive in confined micro-spaces [13] between flexible elastic boundaries such as vessel walls or soil pores [14], and indeed in the human body, where they account for over 80% of microbial infections [15]. Biofilms are difficult to treat with antibiotics, being thousands of times more resistant than the constituent microorganisms in isolation [16] due to a range of mechanical and biological processes [17,18].…”
mentioning
confidence: 99%